Antioxidant Activities of Heracleum platytaenium extracts and Essential Oil - Tunay Karan; Nusret Genc (Turkish Journal of Agriculture: Food Science and Technology)
Heracleum platytaenium Boiss. has been used in traditional medicine. Antioxidant effect of essential oil as well as extracts of H. platytaenium was investigated. The essential oil was acquired by hydro distillation using a Clevenger type apparatus and GC-MS was used to analyze the essential oil compounds. Antioxidant capacity including ABTS+•, DPPH• scavenging and reducing power activity tests were carried out for essential oil and extracts. Moreover, total phenolic and total flavonoid contents were investigated. n-Octyl acetate (36.5%), apiole (24.9%), and elemicin (20.8%) were the chief products of essential oil. The essential oil and extracts exhibited from weak to moderate activity. The total phenol varied from 19.01 to 130.99 mg GAE/g extract and total flavonoid was fluctuated from 2.0 to 118.4 mg QE/g extract. The most DPPH• scavenging effect was observed in EtOAc extract (IC50 = 24.09 mg ml –1). The ABTS•+ scavenging effect of EtOAc extract was better than synthetic antioxidants BHA, BHT and Trolox.